Putting Fetal Alcohol Spectrum Disorder (FASD) on the Map in New Zealand: A Review of Health, Social, Political, Justice and Cultural Developments. Issue 6 (2nd November 2017) - Gibbs, Anita; Sherwood, Kesia
Abstract : The damaging effects of alcohol intake have long been recognised as an issue for New Zealand society since the introduction of alcohol by early settlers. In the mid-1990s, New Zealand began to acknowledge the distinct set of impairments that result from prenatal alcohol exposure that is now known as fetal alcohol spectrum disorder (FASD), which affects all facets of an individual's life, including having individual impairments as well as secondary disabilities arising from those impairments. In New Zealand, a collaborative, multidisciplinary and multiagency approach has been necessary in order to offer the best support for individuals and families who are living with FASD. In this article, the developments within New Zealand's health, justice, social and cultural sectors are traced and the work of many individual trailblazers who have put FASD on the map is acknowledged. The story of putting FASD on the map in New Zealand is one of determination, hope and opportunity, as well as recognition that there is still a long way to go.